2008
DOI: 10.1007/s00424-007-0439-4
|View full text |Cite
|
Sign up to set email alerts
|

A structural motif in the C-terminal tail of slo1 confers carbon monoxide sensitivity to human BKCa channels

Abstract: Carbon monoxide (CO) is a potent activator of large conductance, calcium-dependent potassium (BK Ca) channels of vascular myocytes and carotid body glomus cells or when heterologously expressed. Using the human BK Ca channel alpha1-subunit (hSlo1; KCNMA1) stably and transiently expressed in human embryonic kidney 293 cells, the mechanism and structural basis of channel activation by CO was investigated in inside-out, excised membrane patches. Activation by CO was concentration dependent (EC50 approximately 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 27 publications
1
64
0
Order By: Relevance
“…However, how heme binds and whether CO stimulates K ϩ efflux in a heme-dependent or heme-independent manner has still to be established. A cytochrome c-type CXXCH motif is present rather than the typical HRM (45)(46)(47)(48). Further studies are also required to establish the physiological relevance of the apparent heme-mediated inhibition of the arginine transferase activity of R-transferase and of putative heme binding to stanniocalcin glycoprotein hormones (52)(53)(54).…”
Section: Non-nr Heme Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how heme binds and whether CO stimulates K ϩ efflux in a heme-dependent or heme-independent manner has still to be established. A cytochrome c-type CXXCH motif is present rather than the typical HRM (45)(46)(47)(48). Further studies are also required to establish the physiological relevance of the apparent heme-mediated inhibition of the arginine transferase activity of R-transferase and of putative heme binding to stanniocalcin glycoprotein hormones (52)(53)(54).…”
Section: Non-nr Heme Sensorsmentioning
confidence: 99%
“…Studies on a peptide containing the CXXCH motif (which binds heme by His coordination) led to a conclusion that heme is the CO-binding site (45). However, mutating the CXXCH motif His did not diminish the effect of CO on channel permeability (despite heme loss), possibly because CO might also interact with an unidentified metal cluster (46,47). It was also proposed that BK channels do not bind heme but that CXXCH motif cysteines form a thiol/disulfide redox switch, similar to that proposed for Rev-erb␤ (48).…”
Section: Cellular Homeostasismentioning
confidence: 99%
“…Conversely, the upregulation of the channel function in specific cell types may offer protection against some of the aforementioned disorders [107][108][109][110]. The BK Ca channel activity is subjected to modulation by a wide spectrum of biologically relevant factors such as Ser/Thr/Tyr phosphorylation, Cys/Met oxidation, steroid hormones, and diatomic gases (O 2 , NO, and CO) [111][112][113][114]. The PKG-dependent activation of the Na þ /Ca 2þ exchanger by CO has been proposed [12]: this may increase the submembrane Ca 2þ concentration in the vicinity of the BK Ca channels with their consequential opening [115].…”
Section: Co Signalingmentioning
confidence: 99%
“…In addition to the PKG-dependent mechanism, it has been suggested that CO directly stimulates BK Ca channels, implicating that the channels themselves are gas sensors [116]. CO, administrated as a gas or as CO-releasing molecules (CORMs) [117], increases the probability of channel opening [118][119][120] even in cell-free membrane patches [112,114,121], thus suggesting the possibility that CO modulates the channel directly or indirectly through entities intimately associated with the channel proteins, possibly in the same macromolecular complex [116].…”
Section: Co Signalingmentioning
confidence: 99%
“…There are many proposed cellular targets of CO including soluble guanylate cyclase (sGC) [24] and mitogen-activated protein kinases (for review, see [25]). Recent experiments have also shown CO to play important roles in cardiovascular function [26] and O 2 sensing [27,28] via an activation of large-conductance, calcium-activated potassium channel (BK Ca ). Other ion channels have also been shown to be modulated by CO such as L-type calcium channels (Ca v 1.2) [29], TREK-1 [30] and ENaC channels [31].…”
Section: Introductionmentioning
confidence: 99%